I'll walk alone [compact disc, unabridged] - Clark, Mary Higgins (Clark, Mary Higgins. Alvirah and Willy., 2011)
Thirty-two year old Alexandra Moreland is a rising star in the architectural world and lives in Manhattan. But when she is plagued by identity theft, her successful life is turned upside down. Someone has gained access to her bank accounts, credit cards, personal background, and is now impersonating her. Then, with overwhelming circumstantial evidence stacked against her, Alexandra is arrested for the murder of a woman she claims she's never met. Or has she?